Wiley IFRS 2007 : interpretation and application of international accounting and financial reporting standards - Epstein, Barry Jay; Jermakowicz, Eva K. (Hoboken, N.J. : John Wiley & Sons, 2007)
This title provides the useful tools for understanding the IASB standards and offers practical guidance and expertise on how to use and implement them. It incorporates current scholarship and insightful analysis and provides an introduction to game theory as a model for analyzing international relations.
Includes index.
nmn,15/3/18
Loans
Keywords: Accounting; International business enterprises; International financial reporting standards; IFRS